The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3324/haematol.2020.264085
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of hematopoietic <i>JAK2</i> V617F in the development of aortic aneurysms

Abstract: JAK2V617F is the most frequent driver mutation in myeloproliferative neoplasms (MPNs) and is associated with vascular complications. However, the impact of hematopoietic JAK2V617F on the aortic aneurysms (AAs) remains unknown. Our cross-sectional study indicated that 9 (23%) out of 39 MPN patients with JAK2V617F exhibited the presence of AAs. Next, to clarify whether the hematopoietic JAK2V617F contributes to the AAs, we applied a bone marrow transplantation (BMT) with the donor cells from Jak2V617F transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Until now, little was known about the impact of JAK2V617F mutation on aortic aneurysm disease. Findings from a recently published study in angiotensin II-infused chimeric hypercholesterolemic Apoe −/− mice, which took place while we conducted our study, agree with ours regarding the association between the JAK2V617F mutation and aortic aneurysm 29 . Yet, their experimental model was not clinically relevant and did not recapitulate the human disease.…”
Section: Discussionsupporting
confidence: 92%
“…Until now, little was known about the impact of JAK2V617F mutation on aortic aneurysm disease. Findings from a recently published study in angiotensin II-infused chimeric hypercholesterolemic Apoe −/− mice, which took place while we conducted our study, agree with ours regarding the association between the JAK2V617F mutation and aortic aneurysm 29 . Yet, their experimental model was not clinically relevant and did not recapitulate the human disease.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, treatment of vasculopathies in AD-HIES remains a challenge and studies on primary prevention of vascular complications in these patients are limited (5). In this regard, a recent study has identi ed JAK-STAT-pathway dependent alterations of the hematopoietic system on the onset and development of aortic aneurysms in patients (45). Furthermore, Yokokawa et al demonstrated the positive effects of ruxolitinib in preventing aneurysm formation in a murine model (45).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent study has identi ed JAK-STAT-pathway dependent alterations of the hematopoietic system on the onset and development of aortic aneurysms in patients (45). Furthermore, Yokokawa et al demonstrated the positive effects of ruxolitinib in preventing aneurysm formation in a murine model (45). In STAT1 GOF patients, refractory CMC as well as a variety of autoimmune manifestations have clearly improved or resolved under ruxolitinib therapy in several patients (18-23).…”
Section: Discussionmentioning
confidence: 99%
“…As will be reviewed here, the evidence implicating CH in poor cardiovascular outcomes is extensive, which is likely a primary driver for the association of CH with decreased OS in the general population [16]. The relationship between CH and coronary artery disease (CAD) was the first non-oncologic outcome to be recognized [15], with further cardiologic studies also linking CH to progression of heart failure [17][18][19][20], aortic aneurysm [21], pulmonary hypertension [22], deterioration from cardiogenic shock [23], aortic stenosis [24], poor outcomes after TAVR [25] or orthotopic heart transplantation [26], and increased sensitivity to cardiotoxic chemotherapy [27]. Here we will review the evidence connecting CH to cardiovascular outcomes, mechanistic explanations, potential practice changes, and future research directions.…”
Section: Introductionmentioning
confidence: 99%